President’s Message - Ferguson, Cathleen; Hollett, Sharon (Operating Room Nurses Association of Canada Journal, 2021)
Outgoing President's Message When I took on the ORNAC President position, in 2019, I knew it would be a challenge. But who would ever have dreamed that Covid-19 would happen and that the world as we knew it would change. I am so proud of each and every perioperative nurse that stepped up to the challenge, adapted, and provided safe & compassionate care during these difficult times. I have never been prouder to be a Canadian perioperative nurse. Incoming President's Message My first ORNAC National Conference was in Winnipeg in 2003. I was very new to perioperative nursing and was amazed to see the great number of delegates that attended. The speakers and topics were informative. The vendor hall was interactive and felt huge. Networking and making new alliances from across Canada was so valuable. And the fun that we had after hours! Every two years, for decades, ORNAC members from across Canada have gathered together to celebrate our profession. But this year conference was remarkably different. I am proud to say ORNAC’s first ever virtual conference was a resounding success!